Thank you for being late [compact disc, unabridged] : an optimist's guide to thriving in the age of accelerations - Friedman, Thomas L. (Macmillan Audio, 2016)
A field guide to the twenty-first century, written by one of its most celebrated observers. Thomas L. Friedman shows that society has entered an age of dizzying acceleration, and explains how to live in it.